Produksif Jamur Tiram (Pleurotus Ostreatus) Pada Media Tanam Ampas Tahu - Geli, Geli Kulla (Median : Jurnal Ilmu Ilmu Eksakta, 2025)
Abstract This research aims to evaluate the effect of planting media on the growth and production of white oyster mushrooms (Pleurotus ostreatus). The method used was a Randomized Block Design (RAK) with treatment varying the concentration of tofu dregs, namely 0%, 10%, 20%, 30%, and 40%, each consisting of 3 replications with each replication totaling 25 bag logs. Each treatment consisted of 15 baglogs, so the total was 75 baglogs. The results showed that the addition of 20% concentration of tofu dregs resulted in optimal mycelium growth, as well as increasing the number of capped stems, number of pinheads, and weight of oyster mushrooms. Thus, it can be concluded that tofu dregs are effective in increasing oyster mushroom productivity. In addition, this research also identified that the use of tofu dregs not only increases harvest yields, but also contributes to reducing organic waste by utilizing tofu dregs which are usually wasted as a planting medium. This shows that oyster mushroom production can be done sustainably. These findings open up opportunities for innovation in mushroom cultivation and agricultural waste management.